2012
DOI: 10.1007/s12105-012-0362-7
|View full text |Cite
|
Sign up to set email alerts
|

The Role for Surgical Management of HPV-Related Oropharyngeal Carcinoma

Abstract: Human papillomavirus (HPV)-associated oropharyngeal carcinoma has become the predominate cause of oropharyngeal carcinoma in the United States and Europe. Management of this disease is controversial. Traditional open surgical techniques gave way to concurrent chemoradiotherapy following several American and European organ-preservation trials suggesting that both modalities were equally efficacious. More recently, minimally invasive surgical techniques have gained popularity. These techniques provide an opportu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 33 publications
(47 reference statements)
2
22
0
Order By: Relevance
“…In many centers, this evidence has led to the development of a dogma that most, if not all, patients with potentially curable HPV‐driven oropharyngeal SCC should be managed with first‐line CRT. However, this dogma ignores increasing evidence that surgery for HPV‐driven tumors offers equivalent, if not improved, survival benefits . Currently, there is no evidence to support the first‐line use of CRT over surgery for patients with T1 to T2 HPV‐driven tumors .…”
Section: Discussionmentioning
confidence: 99%
“…In many centers, this evidence has led to the development of a dogma that most, if not all, patients with potentially curable HPV‐driven oropharyngeal SCC should be managed with first‐line CRT. However, this dogma ignores increasing evidence that surgery for HPV‐driven tumors offers equivalent, if not improved, survival benefits . Currently, there is no evidence to support the first‐line use of CRT over surgery for patients with T1 to T2 HPV‐driven tumors .…”
Section: Discussionmentioning
confidence: 99%
“…16 The technique improves visualization and adds degrees of freedom to surgical movements. Complication rates are low 17 and swallowing function remains high. 8, 17, 18 Initial, limited HRQOL data has shown that speech, eating, social and overall QOL domains tend to decrease from baseline, but remain high at 3 months post-TORS.…”
Section: Introductionmentioning
confidence: 99%
“…Complication rates are low 17 and swallowing function remains high. 8, 17, 18 Initial, limited HRQOL data has shown that speech, eating, social and overall QOL domains tend to decrease from baseline, but remain high at 3 months post-TORS. 18 However, long term results with significant patient numbers are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…TORS provides an alternative treatment option for oropharyngeal SCC. Although techniques, such as transoral laser microsurgery, have been used for decades, TORS has a favorable learning curve and provides technical advantages, such as increased degrees of freedom with the instruments . Surgery provides valuable pathologic information that can be used to guide adjuvant therapy .…”
Section: Discussionmentioning
confidence: 99%